How do you simplify #2x(x^2-3)#?

2 Answers
Apr 17, 2017

Answer:

See the entire solution process below:

Explanation:

To simplify this expression multiply each term within the parenthesis by the term outside the parenthesis:

#color(red)(2x)(x^2 - 3) = (color(red)(2x) xx x^2) - (color(red)(2x) xx 3) = 2x^3 - 6x#

Apr 17, 2017

Answer:

#2x^3-6x#

Explanation:

Apply the distributive property

#color(red)(2x)(x^2-3)=color(red)(2x)(x^2)-color(red)(2x)(3)#

#color(red)(2x)# is the same as #color(red)(2x^1)#

So #color(red)(2x)(x^2)-color(red)(2x)(3)=color(red)(2x^color(green)1)(x^2)-color(red)(2x)(3)#

To multiply #color(red)(2x^color(green)1)# and #x^2# add the exponents of the #x# terms, so,

#color(red)(2x^color(green)1)(x^2)=2x^(color(green)1+2)=2x^3#

#color(red)(2x^color(green)1)(x^2)-color(red)(2x)(3)=2x^3-6x#

This is your final answer (it cannot be simplified furthermore)